The RRSI (Right Region for Shading Inequalities) - Noriham Bujang; Syah Runniza Ahmad Bakri; Aimi Nuraida Ali Hassan (Malaysia Journal of Invention and Innovation, 2023)
Mathematics is often perceived as a difficult subject, which may discourage some people from learning it. Calculus is a branch of Mathematics that requires prior knowledge of pre-calculus. One topic in pre-calculus is solving a system of inequalities by graphing. The key to solve such problem is by ensuring that the shaded region is correct and follows the inequalities sign. During examinations, students are required to shade the correct region based on a few basic functions such as linear, constant, parabola, and circle. Each function has different inequality signs, which means that students need to shade different regions accordingly. Therefore, this innovation aims to help students to determine the correct region to be shaded more easily. By improving their understanding, this may increase their interest in Mathematics.